압박골절 후유증 관리 중 발생한 섬망 환자 1례 증례보고 - 김주호; Ju Ho Kim; 김경옥; Kyeong Ok Kim; 김헌일; Hun Il Kim; 김근우; Geun Woo Kim; 구병수; Byung Soo Koo (동의신경정신과학회지, 2005)
Delirium is a acute syndrome of disorientation caused by dysfunction of brain tissue and has a many varied symtome. It is characteristic of consciousness disturbance with disorientation and dys-mnesia and emotional disturbance. We experienced a 91 year-old woman who had a sequela of compression fracture as well as unspecified delirium, and whose condition was improved through oriental medical treatment. We had given herb medication, acupuncture treatment and decreased medication to this patient, and observed. The patient's delirium symptom had improved through oriental medical treatment and decreasing medication. It is able to improve a delirium caused by not specified origin and side effect on drug abuse through oriental medical treatment and decreasing medication. KCI Citation Count: 1